Estimation of genetic parameters and genome-wide association study for enzootic bovine leukosis resistance in Canadian Holstein cattle - Renee Bongers; Christina M. Rochus; Kerry Houlahan; Colin Lynch; Gerson A. Oliveira, Jr.; Hinayah Rojas de Oliveira; Nienke van Staaveren; David F. Kelton; Filippo Miglior; Flavio S. Schenkel; Christine F. Baes (Journal of Dairy Science)
ABSTRACT: Bovine leukemia virus (BLV) is the causative agent of enzootic bovine leukosis (hereafter referred to as leukosis), frequently observed in North American dairy herds. Infection with BLV can lead to persistent lymphocytosis and tumors and is associated with decreased production, immunity. and fertility. With no available treatment or vaccine, reducing the prevalence of leukosis through management and culling has not yet been successful. Genetic selection could contribute to permanent improvement in dairy cattle resistance to leukosis. This study aimed to examine the prevalence and impact of leukosis in Canada and to assess the potential for including leukosis resistance in Canadian national genetic evaluations by characterizing the genetic architecture of leukosis resistance using pedigree and genomic information. A total of 117,349 milk ELISA test records on 96,779 Holstein cows from 950 Canadian herds taken between 2007 and 2021 were provided by Lactanet Canada (Guelph, ON, Canada). Each cow was classified as test-positive for leukosis or test-negative for leukosis. Leukosis was present in ∼77% of herds tested; within those herds, an average of 39% of cows tested were test-positive for leukosis. Heritabilities of 0.10 (SE = 0.001) and 0.07 (SE <0.001) were estimated for leukosis resistance using a linear animal model and BLUP or single-step GBLUP methodology, respectively. Breeding value correlations were estimated between leukosis resistance and economically important and phenotypically relevant traits. Most correlations between leukosis resistance and traits already included in Canadian genetic evaluations were favorable, with the exception of SCS. The candidate genes for leukosis resistance identified using a genome-wide association study were on chromosome 23, with some being part of the major histocompatibility complex. This study showed that genetic evaluation for leukosis resistance is possible, and could be considered for inclusion in Canadian national selection indices.